RECENT REVIEW OF THE QUECHERS SAMPLE PREPARATION METHOD FOR FOOD AND ENVIRONMENTAL SAMPLE ANALYSIS - Shinkafi, Isah Yusuf; Lawal, Abubakar; Gwaram, Nura Suleiman; Mashi, Ahmed Lawal (FUDMA JOURNAL OF SCIENCES, 2024)
Creating reliable, environmentally responsible, and effective processes that ensure the traceability, safety, and caliber of their results is one of the main challenges facing researchers doing multi-residue analysis. The QuEChERS  which stands for Quick, Easy, Cheap, Effective, Rugged, and Safe method  has shown itself to be highly adaptable, yielding positive outcomes with a range of analytes. This method allows for versatility in the choice of solvents, salts, and buffers for salting-out partitioning, as well as the use of various sorbents throughout the cleanup process. QuEChERS is a more environmentally friendly sample preparation technique that fits perfectly with analytical chemistry's rising emphasis on sustainability. This review paper's goal is to illustrate the primary applications of the QuEChERS sample preparation method, with a focus on food and environmental investigations. It also covers important improvements in the history of sample preparation methods and offers insights into the classes of substances that have been effectively evaluated with this methodology.